Perancangan Program Layanan di CV. Sejati Berbasis Hasil Evaluasi Metode Kano - Felix Sanders Moelyanto; Kriswanto Widiawan (Jurnal Titra, 2018)
CV. Sejati is a service provider company of machinery and electronics repair, located in Jember, East Java. This project focuses on designing service programme. Service quality in CV. Sejati has indicated to be good by pre-research using servqual method. Designing of service programmes is then searched based on the evaluation of Kano method, which is dividing the service programme into Kano’s categories. Result of the Kano method then could be using to modify the service programmes according to the condition and customer’s needs.